Nitrogen Dynamics of Grain Legume-Weedy Fallow-Flooded Rice Sequences in the Tropics - George, Thomas; Ladha, Jagdish K.; Garrity, Dennis P.; Torres, Rolando O. (Wiley, 1995)
Dry‐season (DS) grain legume‐weedy fallow‐wet‐season (WS) flooded rice is a common cropping sequence in the rainfed lowlands of tropical Asia. To better manage N in this cropping system, we need to understand N dynamics and balances as influenced by the aerobic‐anaerobic soil aeration sequence, legume cropping, biological N2 fixation (BNF), and recycling of legume residues. To understand N dynamics under a range of N derived from BNF (15N‐estimated), harvested in pods and left in residues, we conducted a 2‐yr experiment on a Philippine Alfisol using cowpea [Vigna unguiculata (L.) Walp.], mungbean [V. radiata (L.) Wilcz.], nodulating and nonnodulating soybean [Glycine max (L.) Merr.], and weeds. The main portion of soil mineral N (0 to 60 cm) was NO3 in the dry season and NH4 in the wet season. The sum of soil NO3 and soil N uptake at legume harvest exceeded the decrease in soil NO3 from legume seeding to harvest by 81 kg ha−1, indicating the continued production and legume uptake of soil NO3. The large differences in total N of legumes (46 to 238 kg N ha−1), however, were associated with differences in N derived from BNF (0 to 176 kg N ha−1). When pod N was excluded, legume N balance was, in most cases, negative. The average soil N depletion was 40 kg ha−1 from nonnodulating soybean, compared with 8 kg ha−1 from N2‐fixing legumes. In terms of WS rice grain and N yields, legume cropping did not differ from weedy fallowing, despite greater (by up to 46 kg N ha−1) quantities of legume residue N in some instances. Large amounts of legume residues, however, were associated with reduced legume grain yields, thus decreasing the harvestable grain N output. Fertilizer N, compared with residue N, had a greater effect on WS rice grain and N yields. The use of legumes in lowland rice‐based cropping systems must maximize harvestable N while effectively using soil, BNF, and applied N sources.